SWOT Analysis in SMART ASN Development: A Case Study of HR Development at the Ministry of Manpower of Indonesia - Ichsan Ari Wibowo; Retno Kusumastuti (Budapest International Research and Critics University, 2022)
Competent employees are the strategic advantage of the organization in achieving its performance goals. The Ministry of Manpower (Kemnaker) has made a strategic target for developing human resources, namely SMART ASN, which includes mastery of information technology, foreign languages skills, hospitality traits, and attitudes, ability to build networks, and entrepreneurship. However, the practice of human resource development does not fully refer to the strategic planning agenda. This article explores the perception of how HR employees and stakeholders harmonize HR development with the strategic plan through SWOT analysis. Informants and respondents are functional officials who have the task of collecting and formulating HR policy documents. The results show that there are a number of advantages such as the millennial generation and the weakness is the inadequate direction of HR development policies. On the other hand, the rise of digitalization and its rapid changes are both opportunities and threats for organizations. The author formulated the strategies of strengths-opportunities (SO), weaknesses-opportunities (WO), strengths-threats (ST), and weaknesses-threats (WT). Finally, the author hopes that the article can be an option of recommendations for organizational leaders in human resource development strategies at the Ministry of Manpower.